Tratamiento oncológico y nivel de depresión en un paciente - Parreño Carrera, Tatiana Katherine (2019)
A diagnosis of cancer can be a huge impact for the patient who suffers and their families, feelings of depression, anguish and fear are highly reflected in it. The biological and psychological condition of various diseases seems to favor the appearance of psychological symptoms that often confuse them with the symptoms of the medical illness or with symptoms produced by its treatments. Different techniques were used to collect data and patient history, which were structured in 6 sessions, including the assessment of the different psychometric tests to establish the level of depression and end with a structural diagnosis based on the criteria of the DSM-5. The objective of this research was to design a therapeutic scheme with a rational-emotional approach where goals and techniques are exposed for the possible reduction of depressive symptomatology in different patients who are going through the same problem. It is necessary to highlight the importance of individual psychological accompaniment in hospital centers contributing to the comprehensive rehabilitation of patients undergoing cancer treatment and highlighting the preponderant role of interdisciplinary work (doctor-psychologist). Finally, it is recommended to continue with the collaboration of practitioners of the clinical psychology area in the country's hospitals, mainly at the General Hospital Babahoyo IESS, in this way to contribute to the integral rehabilitation of patients in the oncological area and in turn employ more psychotherapeutic techniques, reducing symptoms from the beginning, preventing the patient from reaching serious consequences